편평상피세포 폐암 환자의 항암화학요법에 의해 유발된 말초신경병증에 대한 한방치험 1례 - 김균하; 김민화; 허기윤; 이찬; 조임학; 강희경; 김소연; 박성하; 윤영주; 이인; 한창우; 홍진우; et al. (대한한방내과학회지, 2021)
The purpose of this study is to report the effect of Korean medicine on a squamous cell lung cancer patient with chemotherapy induction peripheral neuropathy (CIPN). A 61-year old male patient, who had received 4 cycles of chemotherapy after lung surgery from squamous cell lung cancer, was treated with acupuncture and herbal medicines, including Uchasingi-hwan and Samchilchoongcho-capsule, to control CIPN and dyspnea on exertion. The degree of pain was assessed by a numeric rating scale (NRS). After receiving acupuncture and herbal medicines, the NRS score for CIPN symptoms was reduced from 4 to 1 and the NRS score for dyspnea on exertion decreased from 3 to less than 1. Korean medicine could therefore be useful in reducing peripheral neuropathy occurring after chemotherapy and dyspnea after lobectomy.